Gender Equality, Poverty And Economic Growth - Morrison, Andrew R. (The World Bank, 2007)
This paper reviews empirical findings from economic analyses of the role of gender equality and women's empowerment in reducing poverty and stimulating growth. Going beyond the large literature documenting the impact of female education on a range of development outcomes, the paper presents evidence on the impact of women's access to markets (labor, land, and credit) and women's decision-making power within households on poverty reduction and productivity at the individual and household level. The paper also summarizes evidence from studies examining the relationship between gender equality and poverty reduction and growth at the macro level. Although micro level effects of gender equality on individual productivity and human development outcomes have been well documented and have important ramifications for aggregate economic performance, establishing an empirical relationship between gender equality and poverty reduction and growth at the macro level has proven to be more challenging. The paper concludes by identifying priority areas for future research